Port power: Towards a new geopolitical world order. (December 2022) - Noorali, Hassan; Flint, Colin; Ahmadi, Seyyed Abbas
Abstract: Though ports may appear to play a primarily economic role at a local scale, they also are important in global and geopolitical processes. Ports connect the two geographical realms of land and sea as geographic sites with the dual roles of economic gateways and nodes of geostrategic projection. Processes of port urbanization occur within, and are a component of, the dynamic of geopolitical world transitions and orders. A port power is a country that is dominant in eight metrics of port construction, management and control that combine to make it both a major player in the seas, especially maritime transport and naval capability, and with access to the Eurasian landmass. The current moment of geopolitical transition can be understood by considering shifts in port power. The twenty-first century global geopolitical order will be dominated by the country that is the dominant port power and China is currently positioned to take that role.